Kearifan Lokal Masyarakat Cibalong dalam Melestarikan Keanekaragaman dan Pola Bersarang Kelelawar Penghuni Gua di Kawasan Karst Cibalong Kabupaten Tasikmalaya Pada Pengembangan Model Pembelajaran Berbasis Kearifan Lokal di SD: Kearifan Lokal Masyarakat Cibalong dalam Melestarikan Keanekaragaman dan Pola Bersarang Kelelawar Penghuni Gua di Kawasan Karst Cibalong Kabupaten Tasikmalaya Pada Pengembangan Model Pembelajaran Berbasis Kearifan Lokal di SD - Mohammad Fahmi Nugraha (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2016)
The environmental problems at this time, especially the diversity of bat cave dwellers in the karst of Cibalong, Tasikmalaya should be given the special attention by all of the society elements, especially by the educators who must act real and solve the problems to give the view of knowledge to the community and the students in understanding the importance of bats which is considered as a pest and it is associated with mystical things. One of the effort is looking for and implementing some of learning model based on the local wisdom to change and establish the scientific thinking of the sociaety and the students to analyze the presence of bat in term of the survival of the ecosystem. It is expected that bats and their habitats in Karst of Cibalong, Tasikmalaya can be preserved.